ANALISIS KOMPETENSI PROFESIONALITAS GURU PAK DALAM MENINGKATKAN KREATIFITAS BELAJAR SISWA IX SMP NEGERI 1 SIANTAR NARUMONDA TOBA SAMOSIR TAHUN 2017/2018 - Purba, Niki Astrina (IAKN Tarutung, 2018)
Abstract, This study aims to determine the percentage of Professional Teacher Competence Christian Educatin In Improving Student Learning Creativity Class IX SMP Negeri 1 Siantar Narumonda Toba Samosir Year Learning 2017/2018. This research uses descriptive quantitative method. With the research population is all the students of class IX SMP Negeri 1 Siantar Narumonda which amounted to 117 people with samples taken 30% so that the sample in the study of 36 people determined by simple random sampling technique.The data were collected by closed questionnaire as many as 40 items and the instrument validity test results were between 0.465 to 0.816 0.361. Instrument reliability test results obtained are in very strong category.From the results of data analysis obtained value Application of Professional Teacher Competence Christian Educatin In Improving Creativity Learning = 81.64% is in very good category, meaning Christian Educatin teachers have applied Professional Competence In Improving Creativity Learning very well. This research suggests if it will improve students' learning creativity then it is necessary to apply professional competence on learning Christian Religious Education. Keywords: Professional Competence, Learning Creativity